The Influence of the STEM-Based Problem-Based Learning Model on Students' Science Literacy Skills in Science Learning - Arum Zaharani; Syamsurizal; Muhyiatul Fadilah; Moralita Chatri (Postgraduate, University of Mataram, 2026)
This research is motivated by the low level of science literacy among students in Indonesia, including at SMP Negeri 17 Kota Jambi. The study aims to determine the effect of the STEM-based PBL model on the science literacy of seventh-grade students at SMP Negeri 17 Kota Jambi. This type of research is a quasi-experiment with a pre-test post-test control group design. The research sample consisted of two classes: the experimental class (VII C) with 32 students who received the STEM-based PBL model treatment, and the control class (VII E) with 31 students who used the direct instruction model. The research results science literacy skills improved, with an average pre-test score of 58.5 and a post-test score of 79.75, while the control class increased from 38.32 to 60.38. The N-Gain value for science literacy in the experimental class was 50.83 (moderate category), which was higher than the control class's 38.32. The t-test results show a significance value of 0.037 < 0.05, which means there is a significant difference between the two groups. It can be concluded that the implementation of the STEM-based PBL model is effective in improving students' science literacy skills in science learning.